The Plane Simple Shear Testing of Polycarbonate - Gopez, Adolfo Jesus R. (Philippine Engineering Journal; Vol 5 No 1 (1984), 2021)
The plane simple shear test is applied to the case of polycarbonate, an amorphous polymer with a number average molecular weight of 15,600 g/mole and a degree of polydispersity of 1.85. At room temperature, when polycarbonate is in the glassy state (T-145°C), the shear stress-shear strain curve can be divided into five stages. Stage I is characterized by an almost linear variation of the shear stress with the shear strain, and a gradual diminution of the slope towards the end of the stage. Stage II corresponds to a drop in the shear stress even as the increases, while a linear portion of the curve with a small positive constitutes Stage III. A steeper portion of the curve corresponds to IV. Towards the end of the latter stage, the slope of the curve decreases. In Stage V, a progressive reduction of the slope indicates the onset of rupture and a sudden drop in the stress level indicates the end of the test. The yield point has been shown to correspond with the end of Stage I, and microscopic investigation indicates that a shear band forms during Stage II. The band, which is initially short and narrow (0.1 mm), grows in length during Stage II and widens during Stage III. The slope change between Stages III and IV indicates that the band occupies the entire calibrated part of the specimen. The effects of temperatures and strain rate on the shear response was investigated. At low temperatures the stress drop disappeared and a rigid behavior was observed, while at temperatures around and above Tg, a rubbery (elastomeric) response was observe. The strain rate had a weaker although significant effect. Increasing the strain rate increased the observed stress levels. Reversal of the loading mode showed a reduced flow stress and disappearance of the stress drop at yield. Using the test date, an empirical constitutive flow equation for polycarbonate deformed in simple shear was derived. A multiplicative law separating the effects of the different variables was shown to fit the data. A mechanism of plastic deformation based on the nucleation and propagation of defects was proposed and an attempt was made to compare the shear test curve with that of a uniaxial tensile test for polycarbonate using the concepts of equivalent stress and strain. Results of the comparison indicate that these tests cannot yet be derived from each other and that perhaps a better understanding of the basic mechanisms of plastic deformation in glassy amorphous polymers could lead to a more meaningful comparison of the test.